2021
DOI: 10.1021/acsami.1c17770
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Field Effect Transistors: A Sensitive Platform for Detecting Sarin

Abstract: Real time, rapid, and accurate detection of chemical warfare agents (CWA) is an ongoing security challenge. Typical detection methods for CWA are adapted from traditional chemistry techniques such as chromatography and mass spectrometry, which lack portability. Here, we address this challenge by evaluating graphene field effect transistors (GFETs) as a sensing platform for sarin gas using both experiment and theory. Experimentally, we measure the sensing response of GFETs when exposed to dimethyl methyl­phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As recognized by Gosling et al, mobility in graphene can directly influence electrical conductivity and its dependence on carrier density. In this frame, mobility and charge density appear to be intertwined, though an assessment of their relationship still represents a challenging task that can be properly addressed by analyzing experimental data and simulations from GFET devices. In our study, we did not have access to the information provided by a GFET readout, as devices are operated on the basis of chemiresistor read-out scheme (i.e., without a gate). For this reason, we have specifically investigated the change in electron density, but we are aware that a mobility decrease cannot be neglected as an effect leading to the resistivity increase observed in functionalized samples with respect to the pristine one.…”
Section: Gas Sensingmentioning
confidence: 99%
“…As recognized by Gosling et al, mobility in graphene can directly influence electrical conductivity and its dependence on carrier density. In this frame, mobility and charge density appear to be intertwined, though an assessment of their relationship still represents a challenging task that can be properly addressed by analyzing experimental data and simulations from GFET devices. In our study, we did not have access to the information provided by a GFET readout, as devices are operated on the basis of chemiresistor read-out scheme (i.e., without a gate). For this reason, we have specifically investigated the change in electron density, but we are aware that a mobility decrease cannot be neglected as an effect leading to the resistivity increase observed in functionalized samples with respect to the pristine one.…”
Section: Gas Sensingmentioning
confidence: 99%
“…More strikingly, the slope of Δ R / R 0 (green dashed lines) is changing accordingly to the ethanol concentration, which is equal to 7800 ppm in the light red region and 13,700 ppm in the darker red regions. Chemiresistors used in this work have a response time of ~20 min [ 10 ], which is defined as the time required for the sensor in a lab setting to display a signal Δ R/R 0 reaching 90% the maximum signal associated with a constant analyte concentration. For real-life applications, other features, such as the maximum slope of the time-dependent signal, or a comparison between the responses provided by different types of sensors, could be monitored to reduce the time necessary to detect and identify chemicals [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that, when exploring new compact sensing technologies, graphene-based chemiresistors satisfy many requirements for gas sensing applications [ 9 , 10 ]. For example, their lightweight, low power consumption, and chemical stability position them advantageously to play a key role in future sensing technologies [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work also demonstrated their potential in real-life applications, notably by mounting them on a drone and using a control sensor and algorithm able to significantly reduce noise from fluctuating environmental conditions . In addition to being thin and chemically stable, graphene’s conical band structure around the Fermi level ensures that small changes in the electrostatic environment around a graphene chemiresistor result in significant changes in its resistance. , Consequently, graphene sensors have demonstrated high sensitivity toward gases such as ethanol, dimethyl methylphosphonate (DMMP), NO, NO 2 , and NH 3 . Selectivity of such devices, however, is a distinct challenge for which researchers have explored UV illumination and chemical functionalization as new strategies. For example, noncovalent functionalization with aromatic molecules provides graphene’s surface functional groups with the ability to bond to specific molecules while preserving graphene’s electronic properties. , In an array configuration, the functionalization strategy was successfully used for targeted sensing of ammonia and formaldehyde .…”
Section: Introductionmentioning
confidence: 99%